Assessing factor structure and reliability of the career adaptability scale in students with special educational needs - Yang, Lan; Sin, Kuen Fung; Savickas, Mark L. (Frontiers in Psychology, 2023)
Abstract Despite the importance of career guidance and life planning education in helping students' career development, considerably limited research has been done to provide a good educational assessment to identify SEN students' strengths and weaknesses in career adaptability. This study aimed to assess the factor structure of the career adaptability scale in mainstream secondary students with special educational needs. The results support adequate reliabilities of the total scale and subscales of the CAAS-SF among over two hundred SEN students. The results also support the four-factor structure of the career adaptability construct in assessing career concern, control, curiosity, and confidence. We also found its measurement invariance across gender at the scalar invariance level. The positive and significant correlation patterns between boys’ and girls’ career adaptability and its sub-dimensions with self-esteem are similar. Overall, this study support that the CAAS-SF is a good measure with adequate psychometric properties for assessing and developing practical career guidance and life planning activities and programs for SEN students to support their career development needs. Keywords: Career adaptability, career development, CAAS-SF, SEN students, career guidance, and life planning